Fractional Logistic Equation Applied to Brazilian COVID-19 Data - Mendonça, Anne Karoline Feitoza; Souza, Gabriel Matos; Paixão, Denilson Nogueira dos Santos; Amorim, Ronni Geraldo Gomes de; Rispoli, Vinicius de Carvalho (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
In this paper we analyzed a fractional logistic model applied to Brazilian COVID-19 data. In order to solve the logistic model, we presented a modified version of Adams-Bashforth numerical method. All numerical simulations were performed in MATLAB. As a result, the qualitative comparison between the theoretical model and the cumulative confirmed cases showed a great proximity. In this case, the coefficient of determination, 𝑅2, between these data sets, was calculated to be 0, 917, attesting that the fractional model can be used to model real data with quality.
Keywords: Fractional Calculus; Caputo Fractional Derivative; Adams-Bashforth method; Fractional Logistic Equation; COVID-19.